INCREASE PRODUCTION OUTPUT ON TWA 1342 MACHINE WITH OVERALL EQUIPMENT EFFECTIVENESS (OEE) METHOD (CASE STUDY: PT XYZ BATAM) - Vera Methalina Afma; Hery Irwan; Elsa Berliani (Fakultas Teknik, Universitas Riau Kepulauan, 2022)
PT XYZ Batam is a manufacturing company that produces NTC (Negative Temperature Coefficient) Sensors. This company has a Chip Dicing Department which is cutting the NTC substrate into chips and then measuring process, measuring process is checking process based on the chip resistance value by the TWA 1342 machine.Currently, the output of measuring process is not stable, so this study aims to determine the cause of low output and how to increase production output on the TWA 1342 machine with Overall Equipment Effectiveness (OEE) method. The results obtained based on calculations on the TWA 1342 machine are : availability value 95.12%, Performance value 85.06%, Quality value 98.97% and OEE value 80.08%.Based on the Pareto chart, the cause of output target being not achieved was due to a filter was not suitable for use, because there were tears on the surface of the filter so the dirt was not filtered properly. And the action taken based on the fishbone diagram analysis is to replace the filter periodically and control it by having a filter change record.After the corrective steps have been taken, the changes in the OEE value on the TWA 1342 machine for one week of observation are as follows: Availability value 99.69%, Performance value 98.10%, Quality value 99.15%. And the OEE value is 96.96%. The percentage of the total output during the week of observation after corrective steps was taken is 98.10%. Where there is an increase in output of 13.04%.